Advances in health-promoting effects of natural polysaccharides: Regulation on Nrf2 antioxidant pathway - Luo, Jiang-Hong; Li, Jing; Shen, Zi-Chun; Lin, Xiao-Fan; Chen, Ao-Qiu; Wang, Yi-Fei; Gong, Er-Sheng; Liu, Dan; Zou, Qi; Wang, Xiao-Yin (Frontiers in Nutrition, 2023)
Natural polysaccharides (NPs) possess numerous health-promoting effects, such as liver protection, kidney protection, lung protection, neuroprotection, cardioprotection, gastrointestinal protection, anti-oxidation, anti-diabetic and anti-aging. Nuclear factor erythroid 2-related factor 2 (Nrf2) antioxidant pathway is an important endogenous antioxidant pathway, which plays crucial roles in maintaining human health as its protection against oxidative stress. Accumulating evidence suggested that Nrf2 antioxidant pathway might be one of key regulatory targets for the health-promoting effects of NPs. However, the information concerning regulation of NPs on Nrf2 antioxidant pathway is scattered, and NPs show different regulatory behaviors in their different health-promoting processes. Therefore, in this article, structural features of NPs having regulation on Nrf2 antioxidant pathway are overviewed. Moreover, regulatory effects of NPs on this pathway for health-promoting effects are summarized. Furthermore, structure-activity relationship of NPs for health-promoting effects by regulating the pathway is preliminarily discussed. Otherwise, the prospects on future work for regulation of NPs on this pathway are proposed. This review is beneficial to well-understanding of underlying mechanisms for health-promoting effects of NPs from the view angle of Nrf2 antioxidant pathway, and provides a theoretical basis for the development and utilization of NPs in promoting human health.